Effect of Metal Dopant on the Performance of Ni@CeMeO2 Embedded Catalysts (Me = Gd, Sm and Zr) for Dry Reforming of Methane - André L. A. Marinho; Raimundo C. Rabelo-Neto; Florence Epron; Fabio S. Toniolo; Fabio B. Noronha; Nicolas Bion (Methane, 2022)
Biogas upgrading by a catalytic process has been studied in order to obtain syngas using renewable source of methane. This work evaluates the influence of metal dopant (Gd, Sm, and Zr) on the CeO2 structure for the dry reforming of methane over Ni nanoparticle embedded catalysts. The doping with Zr improved the thermal stability of the catalyst, leading to the formation of small Ni nanoparticles, while Ni metal sintering was observed for Ni@CeO2, Ni@CeGdO2, and Ni@SmO2, according to in situ XRD under reduction conditions. The ceria reducibility was affected by the dopant nature, for which the addition of Zr caused distortions in the ceria lattice, promoting the diffusion of oxygen bulk to surface. The doping with Gd and Sm created oxygen vacancies by charge compensation, and the saturation of oxygen vacancies in the fresh samples decreased the degree of Ce reduction, according to TPR results. The larger Ni particles and poor redox behavior for Ni@CeGdO2 and Ni@CeSmO2 were responsible for the high carbon formation on these catalysts during the DRM reaction. The Ni@CeZrO2 catalyst did not present coke formation because of smaller Ni crystallite size and higher ceria reducibility. Therefore, the control of Ni particle size and the high oxygen mobility in the Ni@CeZrO2 catalyst inhibits carbon deposition and enhances the mechanism of carbon removal, promoting the catalyst stability.